2011
DOI: 10.1002/pd.2720
|View full text |Cite
|
Sign up to set email alerts
|

Second trimester serum predictors of congenital heart defects in pregnancies without chromosomal or neural tube defects

Abstract: Abnormal levels of specific second trimester maternal serum biomarkers indicated an increased risk for CHDs among this sample of low risk pregnancies. Our data suggest that future efforts aimed at improving CHD detection in low risk pregnancies may benefit from considering serum biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
2
15
1
Order By: Relevance
“…The discrepancy in our findings may be due to our study using total‐hCG, rather than beta‐hCG, different definitions of CHDs, or because their sample size of 68 CHDs had insufficient statistical power to detect the risk factor. Abnormal levels (both low and high) of second‐trimester hCG have been previously associated with CHDs, providing additional support to our findings that low first‐trimester hCG is associated with CCHDs [Jelliffe‐Pawlowski et al, , , ].…”
Section: Discussionsupporting
confidence: 88%
“…The discrepancy in our findings may be due to our study using total‐hCG, rather than beta‐hCG, different definitions of CHDs, or because their sample size of 68 CHDs had insufficient statistical power to detect the risk factor. Abnormal levels (both low and high) of second‐trimester hCG have been previously associated with CHDs, providing additional support to our findings that low first‐trimester hCG is associated with CCHDs [Jelliffe‐Pawlowski et al, , , ].…”
Section: Discussionsupporting
confidence: 88%
“…All sources are mandated by California law to report diagnosed chromosomal abnormalities (whether diagnosed by karyotype or microarray) to the program. [20][21][22][23][24] Information on CCHDs was collected by the linkage of screening records with all hospital discharge records through 1 year of age for each study infant (wherein records were linked with the use of multiple identifiers [baby and mother date of birth; baby first and last name; mother first, last, and maiden name, address, phone number, and hospital of baby birth]). These records include all inpatient discharge information that is submitted to the state each time a patient is treated in a licensed general acute care hospital in California and includes all diagnoses present at the time of discharge based on 4-or 5-digit codes from the Ninth Revision of the International Classification of Diseases.…”
Section: Methodsmentioning
confidence: 99%
“…43 Jelliffe-Pawlowski et al found, in 2011, an abnormal serum level of a-fetoprotein, hCG, and unconjugated estriol in the CHD group, but the value of first and second trimester maternal serum biochemical markers in screening for fetal CHDs remains to be determined. 44 It is increasingly evident, therefore, that the detection of CHDs in the first trimester is feasible and it is more accurate by adding markers such as NT, TR, and DV reversed a-wave, but early echocardiography is still reserved for those cases considered at high risk for cardiac defects and must not be a routine examination.…”
Section: Congenital Heart Defectsmentioning
confidence: 99%